(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2015)
The existence of Langkasuka and Pattani in history has long been a subject of research by scholars, particularly in relation to being among the earliest civilizations in Southeast Asia. Part of the study is derived from the record of travelers from China, India, Arabia and Europe to the Malay world in the past. However, local communities also possess unique information about the history and origins of Langkasuka and Pattani, including information gleaned from their oral tradition and from their literature. Some of the written material has been published as Hikayat Patani (The Story of Pattani) and Hikayat Merong Mahawangsa (The Tale of Merong Mahawangsa),while some material still exists in the form of Jawi manuscripts, which have not yet been discussed in detail. Preliminary research suggests that information from the local communities has a variety of similarities and differences, as compared to other sources, and this may lead to discussions that are critical to their existence. This paper will discuss Tarikh Fathani (The History of Pattani), which was produced by Sheikh Faqih Ali bin Muhammad bin Shafiuddin in Pattani around the 17th century. The appearance of Tarikh Fathani has led to new insights concerning the origins of Langkasuka and Pattani, which are interesting to talk about, and which could at the same time strengthen or lead to the questioning of the relevance of Malay manuscripts as sources of the socio-cultural history of the nation. Keywords: Tarikh Fathanni Langkasuka, Pattani, Jawi manuscripts